Influence of the Emotional Climate on the Affective Organizational Commitment - Espinoza Ballena, José Antonio (2012)
The impact of emotional events have been much studied in diverse settings: school, home, prisons, sports, etc but only few researches in working settings. The emotional climate is the aggregated of perceptions a person has regarding the affective relationships with his/her environment. These perceptions impact the worker’s attitudes and subsequent behaviors, according to the Affective Events Theory proposed by Weiss and Cropanzano. An instrument was built using a qualitative approach to define the categories and a quantitative analysis of data collected in Peruvian services organizations. The validation process included the correlation of the instrument outcomes with the affective component of the Meyer and Allen model of Commitment, and the moderation effect of the emotional intelligence quotient measured under the Bar-On model.